Mangalap Goar dan Baptisan di HKBP Tobasari: Kajian atas Ambivalensi Makna Antara Budaya Adat dan Ajaran Sakramental Kristen - Lintong Green Light Nababan (Global Education Journal, 2026)
The Batak Toba community in the Sidamanik region still holds a widespread misconception by equating the mangalap goar tradition (customary name-giving ritual) with the sacrament of Baptism in Christianity. This article aims to critically describe the meaning of mangalap goar within Batak culture and compare it with the doctrine of Baptism according to Christian teachings, intending to prevent syncretism among the HKBP congregation. This research employs a qualitative method using a literature study approach combined with in-depth interviews conducted with six informants, comprising traditional leaders, church council members, and lay congregations at HKBP Tobasari Resort Sidamanik. The findings reveal that mangalap goar is essentially a pre-Christian cultural ritual heavily laden with elements of invoking ancestral spirits through the mediation of the datu (shaman), and its primary purpose is to formally validate a person's social identity within the communal framework. Conversely, Baptism is a sacrament of God's grace grounded in the redemptive work of Christ, theologically interpreted as a mystical union with the death and resurrection of Jesus (Romans 6), and functions as the definitive entry into the fellowship of believers. These two constructs share no essential equivalence, either ontologically or soteriologically. Consequently, the church is summoned to deliver comprehensive catechesis to parents and the wider congregation, ensuring that the sacred understanding of Baptism is no longer conflated with local customs, while simultaneously preserving cultural values that do not fundamentally contradict the Gospel. This study underscores the urgent need for contextual theological education to address this ambiguity.